Diffuse large B-cell lymphoma of the small intestine in a refractory coeliac disease - Ahmad Affandi, Khairunisa; Abd Shukor, Nordashima; Mohamed Rose, Isa; Raja Ali, Raja Affendi; Masir, Noraidah (College of Pathologists, Academy of Medicine Malaysia, 2016)
Introduction: Coeliac disease (CD) is a chronic immune-mediated enteropathy induced by dietary gluten in genetically susceptible individuals. These patients have increased risk of lymphomas. Enteropathy-associated T-cell lymphoma (EATL) was previously thought to be the principal malignancy related to CD, however, recent studies show increased incidence of diffuse large B-cell lymphoma (DLBCL) among CD patients. Here, we report a case of concurrent small intestine DLBCL and CD. Clinical case: A 54-year-old Caucasian male who presented with weight loss and persistent diarrhoea was diagnosed as CD following enteroscopy and ileal biopsy. His symptoms however persisted after six months of gluten-free diet. Oesophagogastroduodenoscopy was then performed and showed generalised villous atrophy with scalloping of duodenal mucosa. MR enterography showed small bowel thickening at the proximal and mid-jejunum with mesenteric lymphadenopathies, suspicious of EATL. Repeat enteroscopy one month later showed thickened jejunal wall and biopsy confirmed mucosal disease consistent with refractory CD without features of EATL. A few weeks later, he presented with acute abdomen; laparotomy with small bowel resection was performed for a perforated jejunum. Pathological findings: His first biopsy from the terminal ileum showed severe mucosal flattening of villi with crypt destruction, hence, a diagnosis of CD was made. The second biopsy from duodenum showed severe active duodenitis with blunted villi. Under suspicion for EATL, the third biopsy taken from the jejunum showed villous blunting and flattening, consistent with refractory CD without features of EATL. Subsequently, small bowel resection was performed and gross examination of the perforated jejunum showed thickened wall and a small polypoidal structure. Microscopically, diffuse malignant lymphoid cells comprised of medium to large cells infiltrated the intestinal wall. Immunohistochemical studies showed that the malignant cells were positive towards CD20, CD79α, CD10 (weak), and BCL-6 with a high proliferative index (80%). These cells were negative for CD3, CD5, CD7, CD8, TIA-1, MUM 1, cyclin D1, and CD56; these features were consistent with a diagnosis of DLBCL. Conclusions: Non-responsive CD warrants thorough dietary review and further evaluation to exclude diseases associated with CD such as enteropathy-associated lymphoma or other alternative diagnosis.